2020
DOI: 10.1177/0972753120965083
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Alertness in Medical Students: Effects of a Single Night of Partial Sleep Deprivation

Abstract: Background: Partial sleep deprivation is common among young adults today. Though multiple studies have stressed on the benefits of having a good sleep, medical students often compromise their sleep due to academic targets and stress. This can lead to changes in attention and cognition. The effects of acute partial sleep deprivation of a single night have been studied less and studies in the past in Indian context have shown controversial results that reaction time is decreased following acute partial sleep dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…A Dutch study assessed the attention span of university students with a questionnaire on the ability to concentrate while studying and observed a positive correlation between chronic sleep loss and the ability to concentrate [ 36 ]. Mishra et al analyzed the attention span with the same tool as the present study and observed a reduced reaction time after a single night of sleep restriction [ 37 ]. Pérez-Olmos and Ibáñez-Pinilla compared students on the day immediately following night shifts with students who did not work.…”
Section: Discussionmentioning
confidence: 99%
“…A Dutch study assessed the attention span of university students with a questionnaire on the ability to concentrate while studying and observed a positive correlation between chronic sleep loss and the ability to concentrate [ 36 ]. Mishra et al analyzed the attention span with the same tool as the present study and observed a reduced reaction time after a single night of sleep restriction [ 37 ]. Pérez-Olmos and Ibáñez-Pinilla compared students on the day immediately following night shifts with students who did not work.…”
Section: Discussionmentioning
confidence: 99%
“…There were also some negative effects of nap deprivation on the planning ability. As previously mentioned, planning ability is controlled by the PFC, a brain region particularly vulnerable to sleep deprivation ( 5 , 45 ). However, data have been inconsistent, with some studies demonstrating that executive function is affected by sleep loss and others reporting conflicting results ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Normal social interactions and occupational activities commonly involve the prefrontal cortex (PFC). Importantly, the integrity of the PFC ( 4 ), which may be vulnerable to sleep loss, is vital for planning ability in all aspects of life ( 5 ). Reduced task-related activation in the PFC, which results in impairments in attention and visual networking, is assumed to be the cause of the deleterious effects of sleep loss on executive function ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Partial sleep deprivation may also affect attention. Mishra et al found that partial sleep deprivation had the similar impact on cognition and psychomotor vigilance [ 13 ]. Peszka and Harsh explored the effect of sleep deprivation on event-related potentials (ERP) in non-rapid eye movement sleep (NREM) period, and found that the ERP amplitude in NREM period increased with the increase of sound stimulation intensity and sleepiness degree.…”
Section: Introductionmentioning
confidence: 99%